2010
DOI: 10.1016/j.clinbiomech.2010.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and potential pathomechanics of patellofemoral pain in female athletes

Abstract: Background-The aims of this study were to determine the prevalence and incidence of patellofemoral pain (PFP) in young female athletes and prospectively evaluate measures of frontal plane knee loading during landing to determine their relationship to development of PFP. We hypothesized that increased dynamic knee abduction measured during preseason biomechanical testing would be increased in those who developed PFP relative to teammates who did not develop PFP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
148
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(160 citation statements)
references
References 51 publications
8
148
0
4
Order By: Relevance
“…Previous studies have identified increased hip internal rotation 8 and knee abduction moment 32 as risk factors for PFPS. Although Leetun et al 28 showed that lower isometric hip external rotation strength predisposed collegiate athletes to lower-limb injuries, Thijs et al 44 recently suggested that isometric hip muscle strength might not be a predisposing factor for PFPS in female runners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have identified increased hip internal rotation 8 and knee abduction moment 32 as risk factors for PFPS. Although Leetun et al 28 showed that lower isometric hip external rotation strength predisposed collegiate athletes to lower-limb injuries, Thijs et al 44 recently suggested that isometric hip muscle strength might not be a predisposing factor for PFPS in female runners.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that increased ipsilateral trunk lean may increase the valgus moment of the knee joint. 23,31 Myer et al 32 demonstrated that higher knee abduction moments during landing were associated with a greater incidence of PFPS among female recreational athletes during a basketball season. Also, Hewett et al, 21 based on video analysis of noncontact anterior cruciate ligament injuries in female athletes, reported that greater ipsilateral trunk angle and knee abduction occur in combination.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,7,19,39,40 Thus hip strengthening is often advocated to improve hip mechanics, 26 with the intent of reducing the incidence of, or symptoms related to, PFPS. 4,15,19,27,28 Although it has been shown that these programs improve strength 3,23,28 and reduce or might prevent symptoms, 3,15,21,23,28 it is not clear whether strengthening the hip actually results in improvement of abnormal hip and knee mechanics during functional activities such as running and squatting. …”
mentioning
confidence: 99%
“…39 This movement pattern is thought to increase frontal plane loading of the knee and the dynamic quadriceps angle, resulting in lateral tracking of the patella and abnormal loading of the patellofemoral joint. 6,18,22,27,33,34 Several studies suggest that females with PFPS demonstrate weakness of the musculature that controls hip adduction, hip internal rotation, contralateral pelvic drop, and knee external rotation. 2,4,7,19,39,40 Thus hip strengthening is often advocated to improve hip mechanics, 26 with the intent of reducing the incidence of, or symptoms related to, PFPS.…”
mentioning
confidence: 99%
“…Individuals with PFPS have reported pain and limitations in ability, functioning, and quality of life [5,9]. According to some studies, the PFPS eventually leads to osteoarthritis [10,11].…”
Section: Introductionmentioning
confidence: 99%